2015
DOI: 10.3233/jad-141446
|View full text |Cite
|
Sign up to set email alerts
|

Fully Automated Atlas-Based Hippocampal Volumetry for Detection of Alzheimer's Disease in a Memory Clinic Setting

Abstract: Hippocampal volume is a promising biomarker to enhance the accuracy of the diagnosis of dementia due to Alzheimer's disease (AD). However, whereas hippocampal volume is well studied in patient samples from clinical trials, its value in clinical routine patient care is still rather unclear. The aim of the present study, therefore, was to evaluate fully automated atlas-based hippocampal volumetry for detection of AD in the setting of a secondary care expert memory clinic for outpatients. One-hundred consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 41 publications
0
23
1
Order By: Relevance
“…Brewer et al, 2009;Chupin et al, 2009;Fischl et al, 2002;Leung et al, 2010;Morra et al, 2008;Patenaude et al, 2011), enabling less time-consuming and more reproducible segmentations of the structure. From this perspective, major efforts have been made to provide fully automated methods that could be used in clinical routine (Suppa et al, 2015a(Suppa et al, , 2015b.…”
Section: Introductionmentioning
confidence: 99%
“…Brewer et al, 2009;Chupin et al, 2009;Fischl et al, 2002;Leung et al, 2010;Morra et al, 2008;Patenaude et al, 2011), enabling less time-consuming and more reproducible segmentations of the structure. From this perspective, major efforts have been made to provide fully automated methods that could be used in clinical routine (Suppa et al, 2015a(Suppa et al, , 2015b.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors, using manual methods, automated methods or visual scales, have shown a significant reduction of the volumes of the hippocampus and the entorhinal cortex in both AD and MCI patients [2856]. The atrophy of the hippocampus has been directly related to neuronal loss, and thus can be considered a marker of neurodegeneration [57].…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution MRI studies have shown significant differences in the pattern of hippocampal atrophy in patients with AD compared to normal controls, opening the door to new-generation methods based on the hippocampal subfields [58] or the hippocampal shape [59]. In a previous work, Suppa et al described a scaling method quite similar to ours, and also based on taking a gray matter volume as reference [56]. In particular, they used a set of standard masks for the computation of the gray matter volumes of the left and right hippocampus, which then were scaled to the patient's total gray matter volume.…”
Section: Discussionmentioning
confidence: 99%
“…The examples shown thus far for automated image analyses have been mainly discussed in terms of whole brain analyses, but analyses may also be directed to a specific region, when for example there is an a priori hypothesis for a particular ROI, like the basal ganglia, cerebellum or hippocampus (Glatz et al 2015;Suppa et al 2015;Wu et al 2012). In such circumstances a Bmask^is placed over the ROI, so that comparisons are focused just within the ROI, reducing some of the restrictiveness of family wise error.…”
Section: Overview Of Structural Neuroimaging Analysesmentioning
confidence: 99%